Production of temporary bone scaffold reinforced with OPEFB-CMC from oil palm empty fruit bunch - M. Yusup, Eliza (2015)
Bone fracture is a common injury because of its nature position that is mostly closest to skin and exposed to excessive compression and depression. Current treatment for bone fracture employs the scaffolding approaches which are specifically positioned for a certain period of time. These allow the defective bones to undergo proper healing processes. However, these scaffolds have two issues that need to be addressed; the material’s compatibility and degradability. Previously, there was poor interaction between the Chitosan (CS) and Hydroxyapatite (HA)/nano HA (nHA) phases causing the composite to have poor physico-chemical properties. This research used Carboxymethylcellulose (CMC) as the reinforcement material for CS / HA or nHA composite scaffold. The main objective is to produce CMC from Oil Palm Empty Fruit Bunch (OPEFB) for temporary biodegradable bone scaffold from a combination of CMC, CS and HA/nHA. Series of experiments were done including extracting CMC from the OPEFB, fabricating composite scaffold by a co-solution method followed by freeze-drying approach to produce a porous bone implant. The final procedure was to analyse the CMC and scaffold produced by various analyses and tests including FTIR, SEM, EDX, TGA and compressive-modulus for its mechanical characteristics. The findings indicated that the strength has increased within 32 – 50 kPa with CMC content compared to chitosan scaffold alone which was only recorded at 0.042 – 0.7 kPa. With the additional of Calcium Phosphate the results only recorded from 0.024 kPa until 2 kPa. The composite scaffold was also successfully constructed with lots of pores, allowing the scaffold to demonstrate preferential proliferation and extracellular matrices and generate mineralised bones. The investigation was extended to in-vitro test involving Simulated Body Fluid (SBF) solution to evaluate the biodegradation rate and vi the growing of apatite layer during immersion. The implant had exhibited biodegradation feature parallel to new bone formation. The ability in attracting Calcium (Ca) and Phosphate (P) elements for apatite layer development on its surface was also proven with the calculated value of Ca/P ratio that has identical value with the theory, at 1.67.